Exploring Riparian Vegetation Dynamics and Water Quality Assesment of Welang River – East Java - Irawanto, Rony; Apriliani, Adini; Rahmania, Farhani Nurshafa; Ilyasa, Muhammad Hasan; Retnaningdyah, Catur; Riniwati, Harsuko; Sugiyanto, Sugiyanto; Yanuwiadi, Bagyo; Leksono, Amin Setyo; Soemarno, Soemarno (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2024)
The Welang watershed is a river that authority of East Java Province, located in three administration (Malang Regency, Pasuruan Regency and Pasuruan City). Welang catchment area from upstream to downstream is 511.60 km2, with main river length 40.09 km. The Welang river basin accommodates surface water (57 tributaries) and ground water (79 springs) in the area of Mount Arjuna (3.200 m) and Mount Bromo (2.400 m). Welang river from upstream to downstream have environmental problems. Riparian vegetation is plants that are found growing and on river banks and function as a transitional ecosystem between aquatic and terrestrial habitats. The main target in Global Strategic Plant Conservation (GSPC) is the study of plant diversity, especially in priority threatened habitats. So an initial study of riparian vegetation diversity in the Welang watershed is very important. Riparian areas are useful for maintaining river water quality and potential for environmental phytoremediation. Result this study, diversity of riparian vegetation are 171 species (upstream), 67 species (mid-stream). 37 species (downstream) and 25 species of aquatic (ex-situ) with 40 species of forest terestrial (in-situ). The Welang water quality at upstream contained organic. The middle part has the same content, no an-organic found. Meanwhile, the downstream contained an-organic.